Empagliflozin Ameliorates Preeclampsia and Reduces Postpartum Susceptibility to Adriamycin in a Mouse Model Induced by Angiotensin Receptor Agonistic Autoantibodies - Zhai, Ruonan; Liu, Yuan; Tong, Jiahao; Yu, Ying; Yang, Lin; Gu, Yong; Niu, Jianying (Frontiers in Pharmacology, 2022)
Preeclampsia (PE) is the leading cause of maternal and perinatal morbidity and mortality and also is a risk factor for cardiovascular and kidney disease later in life. PE is associated with oversecretion of autoantibodies against angiotensin II type 1 receptor (AT1-AA) by the placenta into the maternal circulation. Here, we sought to determine the therapeutic value of the sodium-glucose co-transporter 2 (SGLT2) inhibitor empagliflozin (EMPA) in mice with AT1-AA-induced preeclampsia. Pregnant mice were injected with AT1-AA at gestational day (GD) 13 and treated daily with EMPA until GD 19, at which point some of the maternal mice were sacrificed and assessed. The other maternal mice were labored on time and challenged with adriamycin (ADR) at 12 weeks postpartum; their offspring were assessed for fetal outcomes. We showed that EMPA treatment significantly relieved high systolic blood pressure and proteinuria and ameliorated kidney injury in PE mice without affecting fetal outcomes. EMPA also ameliorated podocyte injury and oxidative stress, reduced the expression of SGLT2 and activated the AMPK/SIRT1 signaling pathway in vivo and in vitro. Remarkably, EMPA treatment during pregnancy reduced ADR-induced kidney and podocyte injury postpartum. These findings suggest that EMPA could be a potential pharmacological agent for PE.